1995
DOI: 10.1074/jbc.270.17.9809
|View full text |Cite
|
Sign up to set email alerts
|

Two Distinct Raf Domains Mediate Interaction with Ras

Abstract: A key event for Ras transformation involves the direct physical association between Ras and the Raf-1 kinase. This interaction promotes both Raf translocation to the plasma membrane and activation of Raf kinase activity. Although substantial experimental evidence has demonstrated that Raf residues 51-131 alone are sufficient for Ras binding, conflicting observations have suggested that the Raf cysteine-rich domain (residues 139-184) may also be important for interaction with Ras. To clarify the role of the Raf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
197
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(208 citation statements)
references
References 28 publications
10
197
1
Order By: Relevance
“…Furthermore, the identi®cation of Ras mutants that bind to Raf-1 with high a nity but are defective in Raf-1 activation, suggested that a direct correlation could not be made between the a nity of Raf-1 to Ras-GTP and Raf-1 activation, as would be expected if the sole role of Ras in Raf activation is its recruitment to the membrane (Akasaka et al, 1996). Hence these observations, coupled with recent ®ndings that Ras interacts with two distinct NH 2 -terminal regions of Raf-1, suggests that Ras promotes more than just membrane translocation of Raf, and instead, may also facilitate subsequent events that lead to Raf-1 activation ( Figure 2) (Brtva et al, 1995;Drugan et al, 1996;. The prevailing data indicate that the ®rst Ras binding site (RBS) in Raf-1 (residues 55 ± 131) is required for Raf-1 translocation by Ras, whereas interactions between processed Ras and the second Ras binding site in the cysteine-rich domain (CRD) of Raf-1 are required for full activation of Raf-1 activity by Ras (Roy et al, 1997;Clark et al, 1995;Mineo et al, 1997).…”
Section: Introductionmentioning
confidence: 53%
“…Furthermore, the identi®cation of Ras mutants that bind to Raf-1 with high a nity but are defective in Raf-1 activation, suggested that a direct correlation could not be made between the a nity of Raf-1 to Ras-GTP and Raf-1 activation, as would be expected if the sole role of Ras in Raf activation is its recruitment to the membrane (Akasaka et al, 1996). Hence these observations, coupled with recent ®ndings that Ras interacts with two distinct NH 2 -terminal regions of Raf-1, suggests that Ras promotes more than just membrane translocation of Raf, and instead, may also facilitate subsequent events that lead to Raf-1 activation ( Figure 2) (Brtva et al, 1995;Drugan et al, 1996;. The prevailing data indicate that the ®rst Ras binding site (RBS) in Raf-1 (residues 55 ± 131) is required for Raf-1 translocation by Ras, whereas interactions between processed Ras and the second Ras binding site in the cysteine-rich domain (CRD) of Raf-1 are required for full activation of Raf-1 activity by Ras (Roy et al, 1997;Clark et al, 1995;Mineo et al, 1997).…”
Section: Introductionmentioning
confidence: 53%
“…Raf-1 then stimulates MAPK kinases (MEK1 and MEK2), which in turn activate p42 and p44 MAPK. The important role of the Raf/MEK/MAPK pathway in Ras-mediated transformation of ®broblasts is supported by the observations that kinase-de®cient, dominant negative mutants of Raf-1, MEK and MAP kinases are potent inhibitors of Ras signal transduction and transformation (Kolch et al, 1991;Cowley et al, 1994;Meloche et al, 1992;Westwick et al, 1994;Troppmair et al, 1994;Brtva et al, 1995). Furthermore, since constitutively activated mutants of Raf-1 or MEK cause tumorigenic transformation of NIH3T3 cells (Kolch et al, 1991;Leevers et al, 1994;Stokoe et al, 1994;Cowley et al, 1994;Mansour et al, 1994), activation of the Raf-1/MEK/MAPK pathway alone is believed to be su cient to mediate Ras transformation.…”
Section: Introductionmentioning
confidence: 97%
“…These activation steps may include a conformational change which would relieve the inhibition imposed by the Raf-1 amino-terminus, multiple phosphorylations of CR2 and CR3, and the presence of accessory proteins such as hsp90 and 14.3.3 (Heidecker et al, 1992;Morrison and Cutler, 1997). It has been demonstrated that activation of Raf by Ras requires multiple contacts with both the RBD and the zincbinding region (Brtva et al, 1995;Chuang et al, 1994). While the RBD provides a high a nity site for Ras-GTP, the zinc binding region interacts with Rasfarnesyl and is critical for the activation of the protein kinase (Chuang et al, 1994;Hu et al, 1995;Luo et al, 1997).…”
Section: Introductionmentioning
confidence: 99%